FAM89A and IFI44L for distinguishing between viral and bacterial infections in children with febrile illness. Issue 3 (22nd September 2021) - Tian, Shufeng; Deng, Jikui; Huang, Wenhua; Liu, Linlin; Chen, Yunsheng; Jiang, Yongqiang; Liu, Gang
ABSTRACT: Importance: The current lack of reliable rapid tests for distinguishing between bacterial and viral infections has contributed to antibiotic misuse. Objective: This study aimed to develop a novel biomarker assay that integrates FAM89A and IFI44L measurements to assist in differentiating between bacterial and viral infections. Methods: This prospective study recruited children with febrile illness from two hospitals between July 1, 2018, and June 30, 2019. A panel of three experienced pediatricians performed reference standard diagnoses of all patients (i.e., bacterial or viral infection) using available clinical and laboratory data, including a 28‐day follow‐up assessment. Assay operators were blinded to the reference standard diagnoses. The expression levels of FAM89A and IFI44L were determined by quantitative real‐time polymerase chain reaction assessment. Results: Of 133 potentially eligible patients with suspected bacterial or viral infection, 35 were excluded after the application of exclusion criteria. The resulting cohort included 98 patients: 59 with viral diagnoses and 39 with bacterial diagnoses. The areas under the curve (AUCs) of diagnoses using FAM89A and IFI44L were 0.694 [95% confidence interval ( CI ): 0.583–0.804] and 0.751 (95% CI : 0.651–0.851), respectively. The disease risk score (DRS) [log2 ( FAM89A expression) − log2 ( IFI44L expression)] signature achieved an improved area under the receiver operating characteristic curve (AUC, 0.825; 95% CI : 0.735–0.915), compared with the AUC generated from individual host RNA. A combination of the DRS and the C‐reactive protein (CRP) level achieved an AUC of 0.896 (95% CI : 0.825–0.966). Optimal cutoffs for the DRS and CRP level were –3.18 and 19.80 mg/L, respectively. Interpretation: The DRS was significantly more accurate than the CRP level in distinguishing between bacterial and viral infections; the combination of these two parameters exhibited greater sensitivity and specificity. This study provides information that could be useful for the clinical application of FAM89A and IFI44L in terms of distinguishing between viral and bacterial infections.